Epidemic arboviral diseases: priorities for research and public health - Wilder-Smith, Annelies (The lancet. Infectious diseases, 2017)
Summary For decades, arboviral diseases were considered to be only minor contributors to global mortality and disability. As a result, low priority was given to arbovirus research investment and related public health infrastructure. The past five decades, however, have seen an unprecedented emergence of epidemic arboviral diseases (notably dengue, chikungunya, yellow fever, and Zika virus disease) resulting from the triad of the modern world: urbanisation, globalisation, and international mobility. The public health emergency of Zika virus, and the threat of global spread of yellow fever, combined with the resurgence of dengue and chikungunya, constitute a wake-up call for governments, academia, funders, and WHO to strengthen programmes and enhance research in aedes-transmitted diseases. The common features of these diseases should stimulate similar research themes for diagnostics, vaccines, biological targets and immune responses, environmental determinants, and vector control measures. Combining interventions known to be effective against multiple arboviral diseases will offer the most cost-effective and sustainable strategy for disease reduction. New global alliances are needed to enable the combination of efforts and resources for more effective and timely solutions.
Available online 21 December 2016
Gesehen am 18.06.2018